Prevalence of problematic use of opioids in chronic noncancer pain: a systematic review with meta-analysis - Catarina de Sousa e Silva (2020)
Background and objective: Opioid prescription for chronic noncancer pain is associated with problematic use. We aimed to review and summarize the evidence about the prevalence of problematic use of opioids in adults with chronic noncancer pain. Databases and Data Treatment: A systematic review of the literature was undertaken following Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Meta-analysis was performed to estimate the pooled prevalence rates using a random-effects model and sub-analysis was conducted. Results: Our search identified a total of 784 potentially relevant studies. After a thorough evaluation, 19 papers were included in our qualitative and quantitative synthesis, mostly from the USA. The estimated prevalence of problematic use of opioids in adults with chronic noncancer pain was 36.3% (95% confidence interval: 27.4% - 45.2%; I2 = 99.64%). The method used to identify problematic opioid use was mostly questionnaire. Thirteen studies (68%) presented a low risk of bias. Conclusions: Although significant heterogeneity was present, our study presents an alarming estimate regarding the prevalence of problematic use of opioids among patients with noncancer pain, which deserves special attention from health care professionals and health authorities.